The Effect of Product Quality, Brand Image, and Price on Customer Satisfaction at Kyuwka the Label in Denpasar City - Sari, Ni Made Indira Dian; Sariani, Ni Ketut; Santini, Ni Made (Journal of Governance, Taxation and Auditing, 2026)
Customer satisfaction is one of the key factors for the success of a business. Many business failures occur because customers are disappointed, leading them to seek alternative similar products. Customer satisfaction is influenced by many factors such as product quality, brand image, and price. The problem formulation in this study is how product quality, brand image, and price affect customer satisfaction. This study aims to determine the influence of product quality, brand image, and price on customer satisfaction. The population in this study consists of customers of Kyuwka The Label in Denpasar City, and the sample includes 98 respondents. The research method used is quantitative. Data analysis techniques include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, F Test, and t Test using SPSS version 26. From the research results, it was found that product quality, brand image, and price have a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction, brand image has a positive and significant effect on customer satisfaction, and price has a positive and significant effect on customer satisfaction.